Study of the Effect of the Mobile Floor of the Separator Device on the Cotton Section - Khusanov Makhamatjonovich, Sadi; Makhkamov Mukhamatxonovich, Anvar; Rustam Muradovich, Muradov; Abdusamat Ismanovich, Karimov (International Journal of Psychosocial Rehabilitation, 2020)
The article is theoretically based on the improved design of the cotton separator, in which the mesh surface in the working chamber of the device is resized relative to previous analogs; it is set in motion, and a mathematical model is developed and graphs are constructed.